2019
DOI: 10.1093/femsle/fnz211
|View full text |Cite
|
Sign up to set email alerts
|

Genomic characterization of Vibrio parahaemolyticus from Pacific white shrimp and rearing water in Malaysia reveals novel sequence types and structural variation in genomic regions containing the Photorhabdus insect-related (Pir) toxin-like genes

Abstract: The Malaysian and global shrimp aquaculture production has been significantly impacted by acute hepatopancreatic necrosis disease (AHPND) typically caused by Vibrio parahaemolyticus harboring the pVA plasmid containing the pirAVp and pirBVp genes, which code for Photorhabdus insect-related (Pir) toxin. The limited genomic resource for V. parahaemolyticus strains from Malaysian aquaculture farms precludes an in-depth understanding of their diversity and evolutionary relationships. In this study, we isolated shr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…This results in an out-of-frame insertion of pirA vp and further affects the downstream gene expression of pirB vp [50]. Furthermore, whole-genome sequencing of 40 V. parahaemolyticus isolated from shrimp hepatopancreas and aquaculture water in Malaysia indicated that pirAB vp genes are prone to deletion [51]. Taken together, these results demonstrate the importance of this DNA transposon in the transfer, deletion, and mutation of the pirAB vp -containing gene cluster.…”
Section: Transposases (Orf15 Orf48 Orf55 Orf57 and Orf68)mentioning
confidence: 83%
“…This results in an out-of-frame insertion of pirA vp and further affects the downstream gene expression of pirB vp [50]. Furthermore, whole-genome sequencing of 40 V. parahaemolyticus isolated from shrimp hepatopancreas and aquaculture water in Malaysia indicated that pirAB vp genes are prone to deletion [51]. Taken together, these results demonstrate the importance of this DNA transposon in the transfer, deletion, and mutation of the pirAB vp -containing gene cluster.…”
Section: Transposases (Orf15 Orf48 Orf55 Orf57 and Orf68)mentioning
confidence: 83%
“…The high seafood consumption in Malaysia puts Malaysians at risk of foodborne diseases from seafood, given there is an increased risk of transmission and/or exposure to V. parahaemolyticus. Moreover, the foodborne pathogen has been frequently isolated from various sources such as seafood and the water environments in Malaysia [39,43,44,[61][62][63] (Table 1).…”
Section: Incidence Of Vibrio Parahaemolyticus In Malaysiamentioning
confidence: 99%
“…A quick search was performed across three databases, Embase, Medline, Scopus, and Google Scholar, using the keywords: "prevalence OR incidence OR occurrence AND Vibrio parahaemolyticus AND Malaysia" to determine relevant original articles published between 2005 and 2023. Results from the search found that V. parahaemolyticus are most commonly isolated from seafood such as shellfish [39,41,43,62,[68][69][70][71][72][73][74][75][76] , shrimps [42,63,[68][69][70][77][78][79][80][81] , squids [68,69,72] , fishes [40,44,61,69,72,75,[82][83][84][85][86][87][88][89][90] , and sea cucumber [91] . The pathogen has also been isolated from vegetables [92,93] and environmental sources such as seawater [44,94] , coastal waters…”
Section: Incidence Of Vibrio Parahaemolyticus In Malaysiamentioning
confidence: 99%
See 2 more Smart Citations